2024
DOI: 10.3390/ijms25020987
|View full text |Cite
|
Sign up to set email alerts
|

Induced Pluripotent Stem Cell-Derived Cardiomyocytes Therapy for Ischemic Heart Disease in Animal Model: A Meta-Analysis

Quan Duy Vo,
Yukihiro Saito,
Kazufumi Nakamura
et al.

Abstract: Ischemic heart disease (IHD) poses a significant challenge in cardiovascular health, with current treatments showing limited success. Induced pluripotent derived–cardiomyocyte (iPSC-CM) therapy within regenerative medicine offers potential for IHD patients, although its clinical impacts remain uncertain. This study utilizes meta-analysis to assess iPSC-CM outcomes in terms of efficacy and safety in IHD animal model studies. A meta-analysis encompassing PUBMED, ScienceDirect, Web of Science, and the Cochrane Li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 82 publications
0
4
0
Order By: Relevance
“…The authors demonstrated that cellular therapy was associated with a significantly greater LVEF and fractional shortening (FS). However, no significant differences were noted regarding the mortality and presence of ventricular arrhythmias [140].…”
Section: Induced Pluripotent Stem Cellsmentioning
confidence: 82%
“…The authors demonstrated that cellular therapy was associated with a significantly greater LVEF and fractional shortening (FS). However, no significant differences were noted regarding the mortality and presence of ventricular arrhythmias [140].…”
Section: Induced Pluripotent Stem Cellsmentioning
confidence: 82%
“…Another study further showed that a vascular endothelial cell adhesion glycoprotein, cadherin-5, could enhance the differentiation of human iPSCs into sinoatrial node-like pacemaker cells, highlighting the possibility of developing biological pacemakers [172]. Focusing on the experimental results of iPSC-derived cardiomyocyte transplantation for ischemic heart disease, a recent meta-analysis investigating the efficacy and safety of this approach in animal models demonstrated significant improvement in left ventricular ejection fraction and reduction in left ventricle fibrosis area in animals with iPSC-derived cardiomyocyte treatment compared with those without [173]. More importantly, that study demonstrated no significant difference in mortality and arrhythmia risk between the two groups [173].…”
Section: Pluripotent Stem Cellsmentioning
confidence: 99%
“…Focusing on the experimental results of iPSC-derived cardiomyocyte transplantation for ischemic heart disease, a recent meta-analysis investigating the efficacy and safety of this approach in animal models demonstrated significant improvement in left ventricular ejection fraction and reduction in left ventricle fibrosis area in animals with iPSC-derived cardiomyocyte treatment compared with those without [173]. More importantly, that study demonstrated no significant difference in mortality and arrhythmia risk between the two groups [173]. On the other hand, despite such a strong implication for clinical application, the transplantation of re-engineered cardiomyocytes (so called "second-generation stem cells" [30]) may accompany adverse complications such as tumorigenicity (e.g., teratoma) stemming from vector or cell pluripotency, which is another major concern when harnessing the plasticity of iPSCs in the treatment of ischemic heart disease [167].…”
Section: Pluripotent Stem Cellsmentioning
confidence: 99%
“…Meanwhile, in vivo studies have shed new light for research advancements in the utilization of iPSCs in CM regeneration, which can potentially affect human lifespan by way of extension and productivity. Thus, iPSCs became a landmark development in regenerative medicine tested in vivo [ 25 ].…”
Section: Induced Pluripotent Stem Cell (Ipsc)mentioning
confidence: 99%